Kapabilitas Dinamis Penerapan Gerakan Sumsel Mandiri Pangan (GSMP) di Kota Palembang - Iriani, Atrika; Sutinah, Sutinah; Zubaidah, Siti (Jurnal Publisitas, 2023)
South Sumatra Province implements the Food Self-Sufficiency Movement of the South Sumatra Province through efforts to change the mindset of the community from "buyers" to "producers" covering the cultivation of plants, fish and poultry. However, its implementation still faces many obstacles, including beneficiaries still focusing on their main activities to earn income so that the assistance received has not been utilized optimally, GSMP socialization has not been optimal for beneficiaries, field assistance related to plant and fish cultivation has not been optimal, as well as assistance that has services provided have not been fully adapted to field conditions and beneficiary skills. So it is important to carry out research, which aims to analyze the implementation of the South Sumatra Independent Food Movement Program (GSMP) through 3 (three) dynamic capabilities namely: Thinking Ahead (thinking ahead), Thinking Again (thinking back) and Thinking Across (thinking about the environment). . The analysis techniques used include: Data Condensation, Data Display, and Conclusion Drawing/Verifications. This research is divided into 3 (three) stages. First primary and secondary data collection through interviews, observation and documentation. The results of the follow-up research on the Optimization of the Food Self-Sufficient Sumsel Movement (GSMP), include: utilization of Integrated Social Welfare Data (DTKS) so that beneficiary households are right on target; Maximizing budget support for the Provincial Government, Regency/City, Village, BUMN, BUMD, Private and other Stakeholders in South Sumatra to make the South Sumatra Independent Food Movement successful in order to support the acceleration of poverty reduction in each Regency/City. Optimizing field extension workers and Assistance Officers for Agricultural, Plantation, Livestock and Fishery Economic Improvement to provide guidance and assistance to beneficiary households that have been assisted by GSMP, as well as maximizing the role of Regency/City PKK in assisting GSMP activities.